(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2011)
I argue that the conception of «méconnaissance» put forward by René Girard should be understood in relation to what Popper calls objective knowledge rather than to the classical idea of knowledge as true and justified belief. Objective knowledge considers knowledge as a tool which is open to many uses and abuses. It allows us to make sense of Girard’s claim that «méconnaissance» grows as our knowledge increases and shows that knowledge and «méconnaissance» should not be understood as polar opposites. This suggests a different relationship between «méconnaissance» and revelation, that revelation does not spell the end of «méconnaissance» but rather initiates a different type of relationship between knowledge and «méconnaissance». I try to illustrate this last point with the help of two examples: Ernesto De Martino’s analysis of tarantism in La terra del rimorso and John Rawls’s idea of a veil of ignorance in his A theory of justice.